2013
DOI: 10.3390/molecules181214597
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceutical Value of Black Cherry Prunus serotina Ehrh. Fruits: Antioxidant and Antihypertensive Properties

Abstract: Abstract:In Mexico black cherry (Prunus serotina Ehrh.) fruits are consumed fresh, dried or prepared in jam. Considering the evidence that has linked intake of fruits and vegetables rich in polyphenols to cardiovascular risk reduction, the aim of this study was to characterize the phenolic profile of black cherry fruits and to determine their antioxidant, vasorelaxant and antihypertensive effects. The proximate composition and mineral contents of these fruits were also assessed. Black cherry fruits possess a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 43 publications
6
35
0
6
Order By: Relevance
“…(American black cherry). 24 A total polyphenol content of 690 mg 100 g −1 FW in chokeberry and an average of 640 mg 100 g −1 FW in Ribes nigrum were reported by Benvenuti et al 25 A three-to four-fold higher phenolic content (2000 and 1950 mg GAE 100 g −1 FW) in chokeberry and elderberry, respectively, has been reported. 26 However, these values were generated from acetone/water/acetic acid extracts, which are known to over-estimate total phenols.…”
Section: Resultsmentioning
confidence: 87%
“…(American black cherry). 24 A total polyphenol content of 690 mg 100 g −1 FW in chokeberry and an average of 640 mg 100 g −1 FW in Ribes nigrum were reported by Benvenuti et al 25 A three-to four-fold higher phenolic content (2000 and 1950 mg GAE 100 g −1 FW) in chokeberry and elderberry, respectively, has been reported. 26 However, these values were generated from acetone/water/acetic acid extracts, which are known to over-estimate total phenols.…”
Section: Resultsmentioning
confidence: 87%
“…Phytochemicals provide further protection against oxidative damage from free radicals. A large number of studies have indicated that phytochemicals present in fruits, vegetables and herbs, exert their antioxidant effects against oxidative stress through the induction or activation of these endogenous antioxidant enzymes (6)(7)(8)(9). In addition, increased ROS production not only directly damages cells by oxidizing macromolecules, such as DNA and lipids, but also indirectly by triggering mitogen-activated protein kinase (MAPK) signaling pathways (10).…”
Section: Introductionmentioning
confidence: 99%
“…The BB diet showed vasodilator and vasoconstrictor effect on the aorta and this was dependent of the NO metabolic pathway. Other findings also observed vasodilator effect of anthocyanins in the endothelium-dependent relaxation [149152]. …”
Section: Introductionmentioning
confidence: 77%